2017
DOI: 10.1371/journal.pone.0181136
|View full text |Cite
|
Sign up to set email alerts
|

Zinc oxide nanoparticles as a substitute for zinc oxide or colistin sulfate: Effects on growth, serum enzymes, zinc deposition, intestinal morphology and epithelial barrier in weaned piglets

Abstract: The objective of this study was to evaluate effects of zinc oxide nanoparticles (nano-ZnOs) as a substitute for colistin sulfate (CS) and/or zinc oxide (ZnO) on growth performance, serum enzymes, zinc deposition, intestinal morphology and epithelial barrier in weaned piglets. A total of 216 crossbred Duroc×(Landrace×Yorkshire) piglets weaned at 23 days were randomly assigned into 3 groups, which were fed with basal diets supplemented with 20 mg/kg CS (CS group), 20mg/kg CS+3000 mg/kg ZnO (CS+ZnO group), and 12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
35
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(49 citation statements)
references
References 56 publications
4
35
0
4
Order By: Relevance
“…Moreover, evidence has indicated that ZnO NPs exhibit potential applications in the poultry and livestock industries, particularly as a feed supplement in the animal’s diet [9]. Numerous studies have been carried out to verify the potential use of ZnO NPs as dietary supplement in improving the growth performances [20–22], increase in the bioavailability of zinc [23, 24], enhancing the immune response [18, 25, 26], enhancing the antioxidative property [25, 27] and also improving the egg qualities and productions of layer chicken [24, 25, 28]. Nevertheless, to date, data on the use of ZnO NPs produced by microbial synthesis for the applications in animal feed has been scant.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, evidence has indicated that ZnO NPs exhibit potential applications in the poultry and livestock industries, particularly as a feed supplement in the animal’s diet [9]. Numerous studies have been carried out to verify the potential use of ZnO NPs as dietary supplement in improving the growth performances [20–22], increase in the bioavailability of zinc [23, 24], enhancing the immune response [18, 25, 26], enhancing the antioxidative property [25, 27] and also improving the egg qualities and productions of layer chicken [24, 25, 28]. Nevertheless, to date, data on the use of ZnO NPs produced by microbial synthesis for the applications in animal feed has been scant.…”
Section: Introductionmentioning
confidence: 99%
“…The emergence of nanotechnology associated with nanoscale has improved the bioavailability and utilization efficiency of trace elements in animal’s diets [145]. Recently, ZnO NPs have been prominently studied on their effects in animal production and their potential application as a dietary supplement as an alternative to the conventional zinc [22, 142, 146, 147]. Due to their small size, ZnO NPs have been introduced into animal feed to increase and improve the absorption rate of zinc in the gastrointestinal tract, which would increase the uptake of zinc and bioavailability in the animal’s body [19, 24] .…”
Section: Introductionmentioning
confidence: 99%
“…Currently, researchers are focusing on the development of NPs as an alternative to antibiotics due to the increase in multidrug-resistant bacteria. On the other hand, ZnO NPs are also used as a feed supplement in animal diet 7 11 . Zinc is an essential trace element that plays a very important role in the body’s biological function 12 .…”
Section: Introductionmentioning
confidence: 99%
“…As a result of this very small size (high surface area), there have high absorption, reactivity and efficiency than conventional zinc. So, these can be used at very lower doses compared to conventional zinc to enhance the animal performance, immunity, reproduction, act as antimicrobial agent and reducing environmental contamination [2,6,[16][17][18][19][20][21][22][23][24][25][26][27]. Numerous techniques have been evolved for the synthesis of ZnO in nano form such as vapour-liquid-solid (VLS) [28], pulsed laser deposition [29], electro chemical deposition [30], metal vapour transport [31,32], chemical vapour deposition [33], metal organic chemical vapour deposition [34]; the hydrothermal growth approach [35], Mechano-Chemical Method [36], chemical precipitation method [37],and sol-gel method [38,39].…”
Section: Introductionmentioning
confidence: 99%